Midline congenital malformations of the brain and skull (2011)
Considering the complexity of congenital midline abnormalities of the brain, it is mandatory to review and summarize the subject, based on embryologic development, developmental biology, clinical approach, neuroimaging, and molecular genetics. There are still several areas of poor knowledge, confusion, and controversy. Pathogenesis in some cases is not clearly understood, and definitions and limits among different diseases are not apparent. This article reviews several malformations of the skull and brain with the aims of making image interpretation easier, enabling an accurate diagnosis, establishing the prognosis, and aiding in genetic counseling.